Reproduction Health Based on Various Kinds of Women’s Blood in Serat Piwulang Estri and Risalah Al-Mahîd: Philological and Comparative Studies - Musarofah, Siti; Ummi Mahmudah (Journal of Social Transformation and Regional Development, 2021)
It is not only the cycle of menstruation that shows a woman’s reproductive health, but also the color of menstrual blood. Studying ancient manuscripts can add insight. Serat Piwulang Estri and Risalah Al-MahÃ®d are two ancient manuscripts containing various color types of womenâ€™s blood. But the problem is that both manuscripts are written in Javanese and not all women understand Javanese. This study aims to: find out the types of women’s blood mentioned in Serat Piwulang Estri and Risalah Al-MahÃ®d, conduct philology studies by comparing the contents of these texts, and to analyze the relationship between types of women’s blood and women’s reproductive health. The library review method used in this study. The results are: In Serat Piwulang Estri it is mentioned four colors of strong blood and one color of weak blood. In Risalah Al-MahÃ®d, there are three colors of strong blood, two colors of weak blood and one characteristic of weak blood, which is thin. Pink blood is not mentioned in Serat Piwulang Estri but in Risalah Al-MahÃ®d. Yellow blood is considered strong blood in Serat Piwulang Estri but in Risalah Al-MahÃ®d it is considered weak blood.